Carbon dioxide emissions from semi-arid soils amended with biochar alone or combined with mineral and organic fertilizers. - Fernández, José M.; Nieto, M. Aurora; López-de-Sá, Esther G.; Gascó, Gabriel; Méndez, Ana; Plaza, César (The Science of the total environment, 2014)
Semi-arid soils cover a significant area of Earth's land surface and typically contain large amounts of inorganic C. Determining the effects of biochar additions on CO2 emissions from semi-arid soils is therefore essential for evaluating the potential of biochar as a climate change mitigation strategy. Here, we measured the CO2 that evolved from semi-arid calcareous soils amended with biochar at rates of 0 and 20tha(-1) in a full factorial combination with three different fertilizers (mineral fertilizer, municipal solid waste compost, and sewage sludge) applied at four rates (equivalent to 0, 75, 150, and 225kg potentially available Nha(-1)) during 182days of aerobic incubation. A double exponential model, which describes cumulative CO2 emissions from two active soil C compartments with different turnover rates (one relatively stable and the other more labile), was found to fit very well all the experimental datasets. In general, the organic fertilizers increased the size and decomposition rate of the stable and labile soil C pools. In contrast, biochar addition had no effects on any of the double exponential model parameters and did not interact with the effects ascribed to the type and rate of fertilizer. After 182days of incubation, soil organic and microbial biomass C contents tended to increase with increasing the application rates of organic fertilizer, especially of compost, whereas increasing the rate of mineral fertilizer tended to suppress microbial biomass. Biochar was found to increase both organic and inorganic C contents in soil and not to interact with the effects of type and rate of fertilizer on C fractions. As a whole, our results suggest that the use of biochar as enhancer of semi-arid soils, either alone or combined with mineral and organic fertilizers, is unlikely to increase abiotic and biotic soil CO2 emissions.
The following values have no corresponding Zotero field: publisher: Elsevier B.V. accession-num: 24632059
Keywords: Biochar; Carbonates; Inorganic C; Mineral fertilizer; Organic amendment; Soil organic matter

Biological and physico-chemical processes influence cutin and suberin biomarker distribution in two Mediterranean forest soil profiles - Andreetta, Anna; Dignac, Marie-France; Carnicelli, Stefano (Biogeochemistry, 2011)
Recent investigations have shown macromolecules, such as cutins, and suberins as effective markers for above and belowground plant tissues. These biopolyesters contain structural units speciﬁc for different litter components and for root biomass. The aim of this work was to understand the fate of plant organic matter (OM) in Mediterranean forest soils by evaluating the incorporation of cutin and suberin by measuring speciﬁc biomarkers. Soil and plant tissue (leaves, woods and roots) samples were collected in two mixed Mediterranean forests of Quercus ilex (holm oak) in costal stands in Tuscany (central Italy), which have different ecological and edaphic features. Ester-bound lipids of mineral and organic horizons and the overlying vegetation were analysed using the saponiﬁcation method in order to depolymerise cutins and suberins and release their speciﬁc structural units. Cutin and suberin speciﬁc aliphatic monomers were identiﬁed and quantiﬁed by gas chromatographic techniques. The distribution of cutin and suberin speciﬁc monomers in plant tissue suggested that mid-chain hydroxy acids can be used as leaf-speciﬁc markers and a,x-alkanedioic acids and xC18:1 as root-speciﬁc markers. Differences in the distributions of biomarkers speciﬁc for above and belowground plant-derived OM was observed in the two types of soils, suggesting contrasted degradation, stabilisation and transport mechanisms that may be related to soil physico-chemical properties. The acidic and dry soil appeared to inhibit microbial activity, favouring stabilization of leaf-derived compounds, while, in the more fertile soil, protection within aggregates appeared to better preserve root-derived compounds.
Keywords: Cutins; Forest soils; Mediterranean; Soil organic matter; Suberins

Soil microbial community structure and activity in monospecific and mixed forest stands, under Mediterranean humid conditions - Lucas-Borja, M. E.; Candel, D.; Jindo, K.; Moreno, J. L.; Andrés, M.; Bastida, F. (Plant and Soil, 2011)
Aims We investigated the link between tree community composition and soil microbial community biomass and structure in central-eastern Spain. Methods The effects of the forest stand composition on the soil organic matter dynamics and on the structure and activity of the soil microbial community have been determined using phospholipid fatty acid profiles and soil enzymatic activities. Results The soil and litter N and C contents were higher in Pinus nigra Arn. ssp. salzmannii and Quercus ilex mixed forest stands (SBHO) and in long-term unmanaged Pinus nigra Arn. ssp. salzmannii forest stands (SBPC) than in pure Pinus nigra Arn. ssp. salzmannii forest stands (SBPA) and Pinus nigra Arn. ssp. salzmannii and Juniperus thurifera mixed forest stands (SBSJ). The bacterial biomass was significantly higher in SBSJ and SBPA than in SBPC and SBHO. The results show an uncoupling of the soil microbial biomass and its activity. pH is related to microbial biomass and its community structure under a Mediterranean humid climate. Conclusions The tree species seem to affect the biomass of the soil microbial community and its structure. The pH, but not the C/N ratio, is a factor influencing the microbial dynamics, biomass, and community structure.
Keywords: Microbial biomass; phospholipid fatty acids; Soil; Soil enzymes; Soil organic matter; spanish black pine

Characteristic alterations of quantity and quality of soil organic matter caused by forest fires in continental Mediterranean ecosystems: a solid-state 13C NMR study - Knicker, H; Almendros, G; González-Vila, F J; González-Pérez, J A; Polvillo, O (European Journal of Soil Science, 2006)
The variable effect of different types of forest fires on the quantity and quality of soil organic matter (SOM) was analysed by comparing burnt and unburnt soils from six forest ecosystems in central Spain by organic elemental analysis and solid-state 13C nuclear magnetic resonance (NMR) spectroscopy. Whole soil samples were collected 1 to 2 years after the fires and included one site affected by two fires within 2 years. The fire-affected soils showed no common pattern with respect to the amount of additional carbon (Cadd) but at all sites, the fire enhanced the aromatic-C content. The weakest fire intensity resulted in the greatest aromatic-C enrichment factor, EFI(aromatic C) indicating the greatest local accumulation of char. The respective Cadd disclosed an EFI(aromatic C) to EFI(alkyl C) ratio, Bchar, of c.1, which supports a small degree of charring. Extensive combustion and volatilization at stronger fire intensities yielded a decrease of EFI(aromatic C) and an increase in Bchar. These trends are in good agreement with fire intensity and forest fuel combustibility in the various sites and therefore these indices could be used to elucidate the quality and quantity of char input that occurs during and after forest fires. No 13C NMR evidence for substantial inputs from non-charred plant necromass was found for any of the single-burn soils. The large carboxyl-C content of Cadd is evidence of the occurrence of oxidation reactions very shortly after the fire. In comparing the single and double-burn sites, no additional char input was observed for the double-burn site, possibly because of complete combustion of young shrubs and char remains during the second fire. The large O-alkyl-C portion found in Cadd of the double-burn soil is best explained by decreased litter degradation.
Keywords: aromatic C enrichment factor; burnt and unburnt soils; Forest fires; mediterranean ecosystems (voyant); Soil organic matter